Social media marketing impact on Gen Z's brand engagement, awareness and image - Wahyu Artha Kusuma, I Gede; Endayani, Fatmasari; K, Aditya Budi; Khouroh, Umu (Manajemen dan Bisnis, 2024)
The research aims to advance our understanding of the realm of social media marketing and how these dynamics influence consumers' engagement with brands and subsequently shape brand awareness and brand image. The research methodology utilized a rigorous quantitative approach, systematically gathering and analyzing numerical data through structured surveys and statistical techniques to uncover patterns, measure variables, and derive objective conclusions. Respondents consist of people in Bali who used social media to connect with the brand. The total number of respondents for this study is 138. they were particularly used for hypotheses testing. Elements of social media marketing, particularly entertainment and trendiness, play a more significant role in fostering Consumer-Brand Engagement. Additionally, Consumer-Brand Engagement has a notable impact on brand awareness and brand image.